Ship Handling Training for Collision Avoidance: Education via Group Work - Kunieda, Yoshiaki; Shimada, Asami; Kashima, Hideyuki; Murai, Koji (Advances in Social Sciences Research Journal, 2021)
In shipping, which is one of the drivers of the world’s economy, many marine accidents continue to occur, such as ship collisions and grounding. To prevent marine collision accidents, there is a strong demand to improve seafarers’ skills through training. Therefore, practical and simulation training sessions are carried out. However, these cannot be considered sufficient because of cost and time constraints. Therefore, the authors proposed a training method in which a group of students set the situation themselves by adding restrictions on actual cases of ship handling for collision avoidance and then discuss and present it. In this training method, ship training instructor assessment and an anchoring experiment were carried out, both of which obtained good evaluations. The anchoring experiment showed a difference of up to 27.5% in the achievement rate between the proposed training and previous training. Regarding ship handling for collision avoidance, as much as a 45.5% difference in achievement rate was observed. These are considered to have the effect of encouraging active thinking by the proposed training method. In addition, the effect of considering the ship handling for collision avoidance for many situations can be thought. Furthermore, it was considered to be the effect of discussions in group work.